Prevalence of bovine trypanosomosis and tsetse fly density in the Yem special district: a cross-sectional study - Bekele, Dagim; Wang, XiaoLong; Beshir, Ahimedin; Terefe, Endale (Frontiers in Veterinary Science, 2024)
This study assesses the prevalence of bovine trypanosomes and the density of tsetse flies in the Yem Special District, Southern Ethiopia, highlighting the disease's significant impact on livestock health and agricultural productivity. Conducted between May 2022 and January 2023, the cross-sectional survey analyzed 960 blood samples for trypanosomes prevalence and tsetse fly density. Results revealed a 10.63% (9–12%) overall prevalence of bovine trypanosomes, with Trypanosoma congolense (5.83%) and Trypanosoma vivax (4.73%) as the predominant species, and 0.63% of mixed infection. Significant associations were found between trypanosomes and anemia, age, and sex, with higher prevalence rates observed in cattle with poor body condition scores and black-hair coats. The study identified three Glossina species, with Glossina morsitans submorsitans being the most prevalent. The findings underscore the need for integrated vector control strategies, community engagement in disease management, and further research using molecular techniques for deeper understanding and effective control measures. Collaboration among stakeholders is crucial for mitigating the disease's impact on livestock and human populations.